(untitled) (World Bulletin of Management and Law, 2023)
The current research aims to study the complementary relationship between financial culture in its dimensions (a culture of saving, a culture of spending, a culture of entrepreneurial ideas) and financial literacy in its dimensions (financial knowledge, financial behavior, financial attitudes), as the research was applied in a selected sample of insurance companies operating in the market Iraq Stock Exchange, and a set of statistical tools and programs were used to analyze and measure the correlation and influence relationships between the research indicators, which is a method)kurtosis&skewness(,)Amos.v.22(,)Spssv.22(The research reached a number of results, the most prominent of which was the existence of statistically significant correlation and influence relationships between financial literacy and financial literacy.